Equality and efficiency in the labour market: Towards a socio-economic theory of cooperation in the context of a globalizing economy - Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1992)
There is a big trade-off between equality and efficiency according to mainstream economists. From a socio-economic point of view, however, it depends upon circumstances and the precise definition of equality and efficiency. The paper shows that in special situations equality is even a precondition for more efficiency. In an extended transaction cost theory, four types of the employment relationship are developed: markets, hierarchies, social networks, and civil rights. While in markets and hierarchical regimes equality may affect efficiency negatively, social networks and civil right regimes (entitlement) are characterized by egalitarian principles compatible with or even complementary to efficiency. Indeed, market regimes are not superior in any case. The study identifies the context conditions under which the four employment regimes are most effective. – – Zwischen Gleichheit und Effizienz herrscht nach Auffassung der okonomischen Hauptstromung ein groSer Zielkonflikt. Aus soziookonomischer Sicht hangt dies jedoch von den Umstanden und der genauen Definition von Gleichheit und Effizienz ab. Diese Arbeit zeigt, daB in besonderen Situationen Gleichheit sogar Voraussetzung fiir mehr Effizienz ist. In einer erweiterten Transaktionskostentheorie werden vier Typen moglicher Beschaftigungsbeziehungen entwickelt: Markte, Hierarchien, soziale Netzwerke und Biirgerrechte. Wahrend in Beschaftigungsregimes, die durch Markte und Hierarchien gekennzeichnet sind, Effizienz durch Gleichheit negativ beeintrachtigt werden kann, sind Beschaftigungsverhaltnisse im Rahmen sozialer Netzwerke und elementarer Biirgerrechte durch egalitare Prinzipien charakterisiert, die mit Effizienz kompatibel oder zur Effizienz gar komplementar sind. Marktbeziehungen sind keineswegs in jedem Fall superior. Die Studie identifiziert die Kontextbedingungen, unter denen die vier Beschaftigungsregimes am effektivsten sind.
Keywords: 300